Inventory models for reverse logistics - Yan, Feng (2010)
In this thesis, we analyze and develop solution methodologies for several inventory models that arise in reverse logistics. The first model we consider is a product recovery system with deterministic demand and return. It is assumed that recovered items (recoverable items that are returned and remanufactured) are as good as new and satisfy the same demand as new items. The demand rate and return fraction rate per unit time are constant and known in advance. The relevant costs are setup cost for remanufacturing recoverable items, setup cost for manufacturing, holding cost for recoverable (or returned) items in stock, and holding cost for serviceable (i.e. newly manufactured or remanufactured/recovered) items in stock. The objective is to minimize the long run average total costs.